The polish Police and its educational role in the context of changes in post-modern global society = Polska policja i jej edukacyjna rola w kontekście przemian w ponowoczesnym społeczeństwie globalnym - Magda, Ernest; Zygadło, Andrzej (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Ever-changing society in the global world requires modern functioning of all organizations. Uniformed services which want to properly fulfill their tasks in a knowledge-based society must participate in the process of permanent change. Apart from its basic functions, such as prevention and repression, the police also have an educational function. The mission of the Polish police in recent years has had to be redefined in the spirit of Community Policing. Contemporary police officers must actively cooperate with their local environment, becoming not only participants but also creators of changes. Recommendations resulting from the analysis of organizational and substantive conditions of changes in the area of police pedagogy made by the authors are helpful in better shaping of pedagogical culture of police officers. In the global world, the analysed experiences and presented recommendations can be implemented also in other societies.
Keywords: post-modern society; organisational culture; Polish police; pedagogical culture; education; educational activities; preventive activities; społeczeństwo ponowoczesne; kultura organizacyjna; polska policja; kultura pedagogiczna; edukacja; oddziaływanie wychowawcze; działalność wychowawcza; działalność profilaktyczna